Identificação e classificação de áreas úmidas em cabeceiras de drenagem - Chapada do Araripe, nordeste do Brasil - Silva, Mirelle Oliveira (2022)
The Brazilian Semi-arid is marked by the low rainfall rates, associated with long periods of drought. Yet, even showing these characteristics, due to its vast environmental diversity, the region has small areas which, in most part, shows constant humidity, like flooded soils accompanied by phytophysiognomy addapted to these saturation conditions. These spaces are commonly called Wetlands (WLs). These environments are spread over several regions of the planet, and they have the most varied sizes. However, in dry climate regions, these areas, broadly, are small, but work as access points for people who live nearby, in addition to functioning as shelter for many animal species, specially in drought periods. In this sense, the studies about the WLs show substantial importance. For this matter, sought to develop this work with the objective of identify and classify the wetlands associated with the headwaters in Araripe plateau, Brazilian northeast. For this study to be carried out, based on this objective, acquisition of cartographic bases of digital origin (vector and raster) were carried out, as well as were produced thematic maps; the planning and determination of the points to be visited were done, posteriorly was defined and carried out the reconnaissance of the WLs, still were stablished the environmental parameters and the representative points, then there was the choice of the representative WLs and at last the characterization and classification of the WLs. From the development of these steps, the results were obtained. These pointed to an existing relation between the hydrogeological and hydrogeomorphologic conditions, especially, in the development and maintenance of WLs in Araripe plateau. Among the applied parameters, the TWI, the curvature of the ground, the slope and the altitude remained constant, proving opportune to the study related to WLs in headwaters areas. Beyond that, another highlighted point in the WLs characterization was the intense usage of earth, once they are environments that have a greater water supply, this fact may be associated with the intermittence, that 4 from the 6 wetlands presented. Concerning the classification, stands out that the Araripe plateau WLs show 4 kinds: plain WLs with channeled valley bottom; plain WLs with not channeled valley bottom; concave WLs with channeled valley bottom; and concave WLs with not channeled valley botom. The classification was carried out through, mainly, the hydrogeomorphological criteria. In this sense, it can be concluded that the Araripe plateau WLs are maintained especially because the hydrogeomorphological and hydrogeological conditions, in this way, the geomorphological parameters are essential for the characterization and classification of the WLs. It was observed the existance of a relation between the intermittent regime WLs and the environmental degradation of the area, and at last that the classification using hydrogeomorphological criteria proved to be efficient, considering the sculptural and hydrological context of the Araripe plateau, broadly.